Use of Cattle-dung as Manure and Domestic Fuel - Sagreiya, K. P.; Venkataramany, P. (Indian Forester, 1962)
Economics of cattle-dung used in India, as a source of domestic fuel and as a fertilizer, are discussed. The consumption and demand trends of energy in India, especially in relation to energy used in house-holds, are reviewed. The production of cow-dung in India, as computed by different authorities, is detailed and it is concluded that about 100 million tons of dry dung (equivalent to 50 million tons of coal) are used as domestic fuel. The burning of cow-dung as domestic fuel is equivalent to destroying annually as much fertlllzer as eight SINDRI fertilizer plants can produce. The manurial value of cow-dung is examined and it is shown to contain ingredients per ton of cow-dung worth Rs. 95/- per ton, while its fuel value is only Rs.40/- per ton. Hence it is concluded that it would be far more economic to use it as manure rather than as fuel. India requires about 25 million tons additional fire-wood annually to meet the shortfall of supplies from unrecorded sources in future years. An extra 100 million tons of fuel-wood is needed to replace cow-dung, bringing the total additional demand to 125 million ton. annually. All this cannot be met by fuelwood plantations. Increased production from primary sources of energy, such as coal, oil, hydro-electric power, lignite and natural gas, is necessary. Assuming that the equivalent of 75 million tons of wood is met by increased production of primary sources coupled with larger yields from State forests as a result of more efficient management of existing forests, the remaining 50 million tons of fuel-wood can be obtained by raising 25 million acres of plantations of fast-growing fuel-wood species. If the cost of planting is Rs.100/- per acre, trees mature in 10 years and on clearfelling can coppice for 5 rotations, the eventual cost of planting is oniy Rs.2/- per acre. Therefore, the maintenance of 25 million acres of plantations would eventually cost Rs.5 crores annually. The rational use of cow-dung for manure and the creation of alternative sources of fuel can be supplemented by recourse to improved chulhas to minimise fuel consumption and dung gas plants to utilise the heat energy without destroying its manurial value. These are briefly described. A detailed bibliography of literature on the subject is appended.